1996
DOI: 10.1002/jor.1100140120
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial tension inhibits tendon collagen degradation by collagenase in vitro

Abstract: Tendon structure is governed largely by factors regulating the anabolic and catabolic phases of tenocyte metabolism. Little is known about the mechanisms that regulate the synthesis, activation, and action of metalloproteinases, which are key enzymes in a multifactorial cascade controlling homeostasis of the extracellular matrix. In the present study, we investigated the effect of tension on collagenase-induced degradation of the tendon in vitro by assessing changes in structural and material properties measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
5
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 16 publications
8
89
5
1
Order By: Relevance
“…Filled data points were included in the fit of P(x) (Supporting Information), returning estimates for the spring constant, k = k B T/σ 2 (effective stiffness of the potential well), the average buckle separation, often occurs without subsequent cleavage but is an obligatory and rate-limiting step in the proteolysis of fibrillar collagen (23). An implication of this model is that degradation will be strongly inhibited by mechanical strain through a switch-like removal of buckle sites (16), consistent with the well-documented, but poorly understood, finding that fibrillar collagen under tension is resistant to degradation by MMP-1, MMP-8, and bacterial collagenase (15)(16)(17)(38)(39)(40)(41). External tension on the fibril would decrease the internal strain energy that drives the formation of buckles.…”
Section: Physiological Implications Of Internal-strain-dependent Defesupporting
confidence: 57%
“…Filled data points were included in the fit of P(x) (Supporting Information), returning estimates for the spring constant, k = k B T/σ 2 (effective stiffness of the potential well), the average buckle separation, often occurs without subsequent cleavage but is an obligatory and rate-limiting step in the proteolysis of fibrillar collagen (23). An implication of this model is that degradation will be strongly inhibited by mechanical strain through a switch-like removal of buckle sites (16), consistent with the well-documented, but poorly understood, finding that fibrillar collagen under tension is resistant to degradation by MMP-1, MMP-8, and bacterial collagenase (15)(16)(17)(38)(39)(40)(41). External tension on the fibril would decrease the internal strain energy that drives the formation of buckles.…”
Section: Physiological Implications Of Internal-strain-dependent Defesupporting
confidence: 57%
“…Normal, physiologic loads are required to maintain tendon homeostasis and prevent excessive degradation of the extracellular matrix [25][26][27] . Nabeshima et al found that culturing nontensioned rabbit patellar tendon explants in the presence of collagenase over a period of twenty hours significantly decreased linear stiffness (p < 0.0001), elongation to failure (p < 0.002), and maximum failure force (p < 0.002) by 80% compared with explants tensioned with constant 4% strain 26 .…”
Section: Tendon Homeostasismentioning
confidence: 99%
“…Nabeshima et al found that culturing nontensioned rabbit patellar tendon explants in the presence of collagenase over a period of twenty hours significantly decreased linear stiffness (p < 0.0001), elongation to failure (p < 0.002), and maximum failure force (p < 0.002) by 80% compared with explants tensioned with constant 4% strain 26 . Further, Flynn et al found that reconstituted type-I collagen micronetworks, strained between micropipettes, degraded significantly slower (p < 0.05) than unloaded controls when exposed to mammalian collagenase matrix metalloproteinase 8 27 .…”
Section: Tendon Homeostasismentioning
confidence: 99%
“…En effet, différents groupes de recherche ont observé une activation des MMP et une expression subséquente ou concomitante de TIMP consécutive à un stress de l'appareil tendineux [7,8]. Certaines observations suggèrent également que la tension axiale protège les fibres de collagène contre la dégradation protéolytique [9]. Bien que le débat entourant la théorie des dommages inflammatoires ne soit pas clos, des travaux récents montrent que l'accumulation maximale des cellules inflammatoires précède le don : macrophages résidents, fibroblastes et mastocytes, qui libéreront une vaste gamme de molécules pro-inflammatoires ( Figure 2B).…”
Section: Blessure Et Réaction Inflammatoireunclassified